Preliminarily Experiments of Liquid Scintillation Cocktail Waste Solidification - Baranyi, Attila; Kopecskó, Katalin (Periodica Polytechnica Civil Engineering, 2022)
Liquid scintillation spectroscopy (LSC) is a widely used laboratory method for measuring radioactive especially low-energy alpha and beta emitter isotopes in solutions. Since the scintillation cocktails (SCs) contain large amounts of aromatic hydrocarbon compounds after the LSC measurement, the sample usually becomes organic radioactive waste, which is challenging to manage and dispose of. The most common and effective waste treatment method is incineration, a costly and cumbersome solution. Another simpler and less expensive way is the immobilization the organic liquids by embedding in cement or geopolymer matrix. The aim of our experiments is to find a universal mix design to solidify and immobilize scintillation cocktail wastes (SCWs) of unknown composition. During the measurement, we assumed that the SCWs could contain Ultima Gold, Ultima Gold LLT, InstaGel Plus and ProSafe FC type scintillation cocktails in pure form or mixed with unknown quantities of water. Therefore, we performed experiments with inactive pure SCs as surrogates to mimic the SCWs. Since the water content determination of the organic solutions is difficult, the mix design must be independent of the water content of SCWs. During our experiments, we found an appropriate mix design to solidify all available SCs up to 5% using CEM I 42.5 N type cement, Metaver N type metakaolin and sodium hydroxide. We could solidify our tested SCW with this mix, and this product meets the waste acceptance criteria of all Hungarian radioactive waste repositories.